Teacher Professional Competency Analysis: Implementation Aspect of Continuous Professional Development (CPD) - Annisa Vidya Safitri; Sutrisno - (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this study was to identify the practice of teacher reflection as the basis for the implementation of Sustainable Professionalism (PKB) program based on Permendiknas No. 16/2007 at SMKN 2 Kediri. This research is qualitative with phenomenology design. The informants of this research are principal, productive teacher of marketing, vice principal, teacher and marketing teacher. Technique of data collecting done by in-depth interview and documentation. The validity of the data using technique triangulation and source. Data analysis using Miles and Huberman interactive models, extension of observation, and referential adequacy. The results showed that the reflection was not used as the basis of CLA and the teachers did not implement the CLA planning. Elements of PKB activities have been in accordance with the guidelines of self-development and scientific publications. PKB activities have an impact on teacher groups that discuss research issues, more varied and contextual KBM, and administrative demands for teachers.